Curcumin-loaded embryonic stem cell exosomes restored neurovascular unit following ischemia-reperfusion injury. (October 2016) - Kalani, Anuradha; Chaturvedi, Pankaj; Kamat, Pradip K.; Maldonado, Claudio; Bauer, Philip; Joshua, Irving G.; Tyagi, Suresh C.; Tyagi, Neetu
Highlights: This is the important study that describes the combined therapeutic potentials of curcumin and embryonic stem cell exosomes. Stem cells have rejuvenating properties and curcumin possesses anti-inflammatory, anti-lipidemic and neurorestoration properties. The combined therapeutic units reduced ischemic injury and restored neuro-vascular unit following ischemia-reperfusion injury in mice. Abstract: We tested whether the combined nano-formulation, prepared with curcumin (anti-inflammatory and neuroprotective molecule) and embryonic stem cell exosomes ( MESC-exo cur ), restored neurovascular loss following an ischemia reperfusion (IR) injury in mice. IR-injury was created in 8–10 weeks old mice and divided into two groups. Out of two IR-injured groups, one group received intranasal administration of MESC-exo cur for 7 days. Similarly, two sham groups were made and one group received MESC-exo cur treatment. The study determined that MESC-exo cur treatment reduced neurological score, infarct volume and edema following IR-injury. As compared to untreated IR group, MESC-exo cur treated-IR group showed reduced inflammation and N -methyl-d -aspartate receptor expression. Treatment of MESC-exo cur also reduced astrocytic GFAP expression and alleviated the expression of NeuN positive neurons in IR-injured mice. In addition, MESC-exo cur treatment restored vascular endothelial tight (claudin-5 and occludin) and adherent (VE-cadherin) junction proteins in IR-injured mice as compared to untreated IR-injured mice. These results suggest that combining the potentials of embryonic stem cell exosomes and curcumin can help neurovascular restoration following ischemia-reperfusion injury in mice.